Sustainability charter and sustainable mobility - Spadaro, Ilenia; Pirlone, Francesca; Candia, Selena (TeMA - Journal of Land Use, Mobility and Environment, 2022)
In order to make our cities more sustainable, the paper describes a research aimed at defining a new urban tool in the context of Agenda 2030. It is the ’Sustainability Charter’, a tool that already exists at the international level, but here is analyses at the local level as a result of decision-making process which refers to a set of interactions between academia (the university), industry and local community. One of the priority of the Sustainability Charter is to analyse all the sustainable services that an administration has to implement in order to help citizens to have virtuous lifestyles. The authors developed a methodological approach to better define, implement and asses these sustainable actions related to different urban topics (mobility, waste management, energy production…). In particular, the paper proposes to adopt different indicators to measure the sustainability of each action using a specific chart defined as sustainability map. The method proposed by the authors aims to be easily adaptable and scalable to different local administrations. To give a concrete example of the results that can be obtained from its application, the paper proposes the experience of the Sustainability Charter of Sestri Levante, a medium-sized municipality in Italy in the Ligurian Riviera. Thanks to this experience, the Municipality of Sestri Levante can improve its mobility-related sustainability services.